Morphometric multiple-scale analysis in the upper basin of the Sauce Corto stream (Buenos Aires, Argentina) (Huellas, 2019)
In the high basin of the Sauce Corto stream (in the Northern watershed of Ventania System in the Province of Buenos Aires), there are frequent extreme precipitation events, which generate floods that affect the socioeconomic development of Coronel Suárez district. In order to infer the hydrological response of the area, it is necessary to analyze the parameters and morphometric indexes that allow for the study of potentially dangerous basins flood. Accordingly, the aim of this paper is to identify variations in the hydrological response of different basins, according to parameters and morphometric indexes obtained from various data and scale sources. The multiple-scale analysis results show the importance of cartographic generalization processes associated to semi detail scaling. In the analysis of the hydrological response it is possible to infer that the use of 1:50.000 scale will possibly underestimate the basins torrentiality and, consequently, its potential danger.
Keywords: Fluvial morphometry; Floods; Sauce Corto; Coronel Suárez.